PRODUCTIVITY TRAITS OF THE NEW VARIETIES AND PROMISING LINES OF SOFT SPRING WHEAT DEVELOPED BY THE TATARSKY RIA - N. Z. Vasilova; D. F. Askhadullin; D. F. Askhadullin; Е. Z. Bagavieva; М. R. Tazutdinova; I. I. Khusainova; G. R. Nasikhova (Зерновое хозяйство России)
The quantitative parameters of productivity of new soft spring wheat varieties ‘Yoldyz’, ‘Idele’, ‘Khayat’ and perspective lines ‘К-43/04-1’, ‘К-48/04-2’, ‘О-192/03-5’ developed by the Tatarsky RIA have been determined in the conditions of the Republic of Tatarstan. The features of productivity formation have been found and the contribution of individual components into productivity formation has been estimated. The number of kernels in the main head is the most significant parameter which affects the productivity. The component of the yield is liable to change because of the conditions of vegetation, the samples of new varieties have shown a strong liner correlation of “kernel yield” with “number of kernels per main head” (r=0,73– 0,85**). The lines ‘К-43/04-1’, ‘К-48/04-2’ and ‘О-192/03-5’ significantly excess the parameters ‘total number of kernels per head’ and ‘number of kernels per spikelet’ of the standard variety ‘Simbirtsit’. It has been shown that the productivity of grain of the studied samples largely depends on the productivity of the above-ground biomass. The correlation of the parameter with productivity was strong enough (r=0,88–0,99**) during all years of study. The correlation ‘1000-kernel weight’ with ‘grain productivity’ was not accurate during all years of study. The breeding work allowed achieving the optimum in the plant structure. All considered varieties and lines mainly form agrocoenosis in the main one-sprout plant, there hasn’t been found any reliable difference in the productive tillering among the samples.